Defining the Structure of Physical Education Lessons in Secondary Schools: A Didactic Problem and Its Solutions - Yurij Vaskov (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. The organization of physical education lessons in secondary schools presents a didactic problem that requires choosing an optimal structure for the training session. This article aims to analyze the theoretical approaches of various scientists towards the typology of lessons, both in general didactic aspect and in relation to the educational subject of Physical Culture.